Natural antioxidant in pig feeding: Effects on meat and on salami quality - Pastorelli G.; Rossi R.; Cannata S.; Corino C. (7th International Symposium on the Mediterranean Pig, 2012)
The purpose of the present work was to evaluate the influence of polyphenols supplementation of diet during the last period of fattening (30 days) on oxidative process and chemical composition of pork and dry sausage. Material and methods. At slaughtering 36 samples of Biceps femoris (BF) muscle from heavy pigs fed control diet or supplemented diet with a natural extract of Verbenaceae (AjuteTM) were collected by each dietary treatment group (n=18). Salami Cremona (PGI) were produced by a local plant according to the Disciplinary of Production and 6 salami for each treatment were submitted to sensory evaluation. Results and conclusion. No differences were found for proximate composition neither in fresh meat nor in salami. The oxidative stability, assessed using thiobarbituric acid reactive substances (TBARS), is lower in fresh meat (P = 0.04) and in salami (P > 0.05) of treated group. Sensory evaluation of Cremona salami discriminated the muscle color (P = 0.04) and the sour taste descriptors (P = 0.02) that resulted more intense in the treated group. The use of natural extracts determined a longer shelf life of meat due to the lower oxidation and a greater colour stability of salami over three months of ripening.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)